Environmental Taxes and the Choice of Green Technology - Krass, Dmitry; Nedorezov, Timur; Ovchinnikov, Anton (Production and Operations Management, 2013)
We study several important aspects of using environmental taxes to motivate the choice of innovative and “green" emissions‐reducing technologies as well as the role of fixed cost subsidies and consumer rebates in this process. In our model, a profit‐maximizing monopolistic firm facing price‐dependent demand selects emissions control technology, production quantity, and price in response to the tax, subsidy, and rebate levels set by the regulator. The available technologies vary in environmental efficiency as well as in the fixed and variable costs. Both the optimal policy for the firm and the social‐welfare maximizing policy for the regulator are analyzed. We find that the firm's reaction to an increase in taxes may be non‐monotone: while an initial increase in taxes may motivate a switch to a greener technology, further tax increases may motivate a reverse switch. For the regulator, we compare the social welfare achievable in the centralized system (which serves as an upper bound) to the highest level achievable under different classes of environmental policies. If the regulator is limited to a tax‐only policy, then when the regulator is moderately concerned with environmental impacts, the tax level that maximizes social welfare simultaneously motivates the choice of clean technology and closes the gap to the upper bound; however, both low and high levels of societal environmental concerns may lead to the choice of dirty technology and significant welfare losses as compared to the centralized case. Supplementing the environmental taxation with fixed cost subsidies and consumer rebates can eliminate this effect, expanding the range of parameters over which the green technology is chosen and often closing the welfare gap to the centralized solution.